2022
DOI: 10.3390/metabo12121282
|View full text |Cite
|
Sign up to set email alerts
|

Receiver Operator Characteristic (ROC) Analysis of Lipids, Proteins, DNA Oxidative Damage, and Antioxidant Defense in Plasma and Erythrocytes of Young Reproductive-Age Men with Early Stages of Type 1 Diabetes Mellitus (T1DM) Nephropathy in the Irkutsk Region, Russia

Abstract: Oxidative stress plays a leading role in the pathogenesis of diabetic nephropathy. However, many aspects of oxidative stress reactions in the initial stages of this disease are not fully understood. The men cohort is of particular interest because of the severe effects of diabetes on their urogenital system. The aim of this study is to assess the intensity of lipids, proteins, DNA oxidative damage, blood antioxidant defense enzymatic, and activity of non-enzymatic components in men with type 1 diabetes mellitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Furthermore, adiponectin promotes high LDL and low HDL concentrations and shows a negative association with BMI, but a positive association with pro-inflammatory cytokines, such as TNF-α and IL-6 [19][20][21]. The lipid profile results obtained in our study were similar to those reported by other Authors who also studied young individuals with T1DM [10,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, adiponectin promotes high LDL and low HDL concentrations and shows a negative association with BMI, but a positive association with pro-inflammatory cytokines, such as TNF-α and IL-6 [19][20][21]. The lipid profile results obtained in our study were similar to those reported by other Authors who also studied young individuals with T1DM [10,22,23].…”
Section: Discussionsupporting
confidence: 89%
“…Its key function is to reduce hydrogen peroxide to water [18]. Darenskaya [19] reported a decrease in GPx activity among diabetics, which we also found in this study. Moreover, in our participants, it was about 20% lower in patients with long duration of T1DM as compared to the early onset group.…”
Section: Discussionsupporting
confidence: 85%
“…More experiments need to be performed in the future if we want to thoroughly prove the above hypothesis. DISCUSSION Previous works have proved that MGO can cause cell oxidative stress by scavenging SOD and glutathione [41][42][43] . The imbalance between ROS generation and antioxidant defense results in the ROS accumulation in cells, and accumulated ROS can damage cellular proteins, lipids, DNA and other biological molecules and cause cell apoptosis [33][34] .…”
Section: Potential Mechanism For the Effect Of Aluas Rna On Mgo-cause...mentioning
confidence: 74%